Developing mathematics problems using local wisdom context of Maluku to improve students’ numeracy - Fahruh Juhaevah (Jurnal Elemen, 2022)
Students' difficulty in solving numeracy problems is a problem that teachers must pay attention. Therefore, it needs media to help students improve their numeracy ability. The purpose of this study is to develop mathematics problems based on PISA (Programme for International Student Assessment) content and use local wisdom context in Maluku that obtained validity, practically, and effectively. Mathematics problems developed are expected to improve the numeration ability of junior high school students in Maluku. The study was research and development based on the Plomp model. The subject consists of 40 students (15 males and 25 females). The result showed that mathematics problems met validity criteria. The validity was tested using the Rasch model that consists of suitable, reliability, difficulty, and differentiation items. Then, it was validated based on experts in content, league, and media. All of them met validity criteria. Mathematics problems had met practically based on the user experience questionnaire (UEQ) that consisted of interest, clarity, efficiency, accuracy, stimulation, novelty, and prospered based on the system usability scale (SUS). Mathematics problems improve the student's numeration ability, as shown based on N-Gain 0.36. Thus, it effectively improves the numeracy ability of students in Maluku.